Perancangan dan Analisa Mesin Sealing Plastik Berbasis Pneumatik - Indra Koto; Heri Al Mughni; Rikardo Sianturi; Maulana Lidung Hasyim; Shapwan Ahmad Raihan Sinaga (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The growth of small and medium-scale food industries necessitates packaging processes that are rapid, neat, and hygienic to enhance product quality and business competitiveness. Common issues associated with manual packaging include imperfect seals, lengthy processing times, and inefficient labor utilization. This study aims to design and analyze a pneumatic plastic sealing machine as a solution to improve the efficiency and quality of food packaging processes. The research methodology involved device design, pneumatic component selection, machine frame fabrication, system assembly, and performance testing. The pneumatic system utilizes an operating pressure of 3 bar to drive the plastic sealing process. Testing was conducted to analyze production capacity, processing time, and seal quality under various operating conditions. The results indicate that the pneumatic plastic sealing machine achieves a production capacity of up to 60 seals per minute. Optimal seal quality was obtained at a heater temperature of 170°C with a sealing time of 1 second, producing a tight, strong, and uniform seal with a 95% success rate. Compared to manual methods, the pneumatic sealing machine increases packaging process efficiency by 50%, delivers superior and consistent seal quality, and enhances overall productivity and process efficiency. This machine represents an effective and efficient appropriate technology solution for small and medium-scale food industries.